The grizzly bear who lost his grrrrr! - Biddulph, Rob (New York: Harper, an imprint of HarperCollinsPublishers, 2016)
Each year, for as long as the forest has stood, a contest is held for the bears of the wood... Fred is the champion. He's the best. But being the best takes time and training, especially when it comes to having the loudest growl. Then, one morning, disaster strikes -- Fred's GRRRRR is gone! Oh, no! Will Fred find his GRRRRR and realize that there's more to life than being a winner?
"Originally published in Great Britain by HarperCollins Children's Books in 2015"--Copyright page.
Ages 4-8.
Accelerated Reader
Keywords: Stories in rhyme; Grizzly bear -- Juvenile fiction; Contests -- Juvenile fiction; Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Competition (Psychology) -- Juvenile fiction; Humorous stories; Grizzly bear -- Fiction; Bears -- Fiction; Contests -- Fiction; Animals -- Fiction; Friendship -- Fiction; JUVENILE FICTION / Animals / Bears; JUVENILE FICTION / People & Places / Polar Regions; JUVENILE FICTION / Sports & Recreation; Animals; Competition (Psychology); Contests; Friendship; Grizzly bear; Humorous stories; Picture books for children; Stories in rhyme; Bears -- Fiction; Picture books for children; Stories in rhyme; Fiction; Humorous fiction; Juvenile works; Picture books; Stories in rhyme; Humorous fiction; Humorous fiction; Stories in rhyme